Severe proteinuria during the administration of bevacizumab plus mFOLFOX6 in a colorectal cancer patient after kidney transplantation: a case report - Ren Onodera; Satoru Nihei; Toshimoto Kimura; Takashi Tomita; Kenzo Kudo (Journal of Pharmaceutical Health Care and Sciences, 2020)
Abstract Background Bevacizumab (BEV) leads to proteinuria and renal damage. It is not clear whether the administration of immunosuppressive drugs after renal transplantation affects the safety of BEV administration. We report a case of severe proteinuria caused by BEV plus 5-fluorouracil, levofolinate, and oxaliplatin (mFOLFOX6) in a patient who had previously undergone kidney transplantation and the administration of tacrolimus. Case presentation The patient was a 67-year-old man with a history of diabetes and hypertension. He developed chronic renal failure 14 years earlier and underwent right kidney transplantation from a living donor followed by the administration of tacrolimus and mycophenolate mofetil for immunosuppression. After kidney transplantation, the patient was diagnosed with colorectal cancer with multiple lung and liver metastases and received BEV plus mFOLFOX6. After 5 cycles, proteinuria was observed, with a urinary protein concentration of > 300 mg/dL (urine protein creatinine ratio: 3.5), and after 16 cycles, the urinary protein concentration was > 1000 mg/dL (urine protein creatinine ratio: 7.1). Subsequently, BEV was discontinued, and only mFOLFOX6 administration was continued. Tacrolimus continued to be administered during chemotherapy. There was no association between serum tacrolimus concentration and proteinuria. Conclusions In this case, BEV administration caused severe proteinuria without affecting blood levels of tacrolimus. Patients with risk factors for renal impairment should be carefully evaluated for the risks and benefits of BEV administration.